The Influence of Price Perception and Product Quality on Solar Panel Purchase Intention Mediated by E-WOM - William Cahya Mulyadi; Liem Bambang Sugiyanto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The solar panel industry in Indonesia is experiencing significant growth in line with increasing energy needs and awareness of renewable energy. However, consumers' purchasing decisions are not only influenced by economic and technical factors, but also by the dynamics of digital communication. This study aims to analyze the influence of Price Perception and Product Quality on Purchase Intention, with Electronic Word of Mouth (E-WOM) as a mediating variable. The study used a quantitative approach through an online survey of 282 respondents, analyzed using the PLS-SEM method. The results of the study show that Price Perception has a positive and significant effect on E-WOM and Purchase Intention, while Product Quality does not have a significant direct effect on E-WOM and Purchase Intention. E-WOM has been shown to play a significant role in increasing Purchase Intention and mediating the relationship between Price Perception and Purchase Intention. The novelty of this research lies in the affirmation of the role of E-WOM as the main mechanism in explaining purchase intention toward solar panels in Indonesia, where the influence of experience and digital recommendations is more dominant than the perception of product quality alone. These findings provide strategic implications for industry players to optimize price value communication and digital reputation management to increase renewable energy adoption intentions.